Perencanaan Pemasangan Pembangkit Listrik Tenaga Surya (PLTS) pada Gedung Departement Teknik Nuklir dan Teknik Fisika Berdasarkan Data Radiasi Matahari dari Aplikasi Revit - Ziaul Fikar; M. Deta Zulfikar Rahman; Sofyan Winardin (Jurnal Teknik dan Science, 2026)
Electrical energy plays a very important role in human life, as almost all aspects of daily activities depend on it. Therefore, the provision of sufficient and sustainable electrical energy is a key factor in improving the quality of human life. Most of the electricity supply in Indonesia still relies on fossil fuels, which are one of the causes of the increase in the Earth’s atmospheric temperature; therefore, the use of carbon-based energy must be reduced. Energy from sunlight can be utilized by developing a Solar Power Plant (PLTS) to reduce the consumption of carbon-based energy. The building selected for the installation of the Solar Power Plant is the Department of Nuclear Engineering and Engineering Physics (DTNTF) building. The DTNTF building is one of the facilities located within the Faculty of Engineering, Universitas Gadjah Mada. On average, almost all buildings at Universitas Gadjah Mada (UGM) are equipped with adequate air conditioning (AC) systems. More than 50% of the electrical energy consumption in UGM buildings is used for cooling lecture rooms and office spaces. Similarly, the DTNTF building is equipped with more than 50 air conditioning units, where each room contains one to two AC units depending on the room size. The remaining electricity consumption comes from office equipment and lighting systems used to illuminate each room in the DTNTF building. Based on these data, the average monthly electricity demand of the DTNTF building ranges from approximately 1,000 kWh to 1,500 kWh. To meet this electricity demand, approximately 30 units of 350 Wp solar panels are required to be installed on the roof of the DTNTF building. Considering the average daily solar irradiation duration in Indonesia of about 5 hours per day, under ideal conditions a 350 Wp solar panel receiving 5 hours of sunlight per day would produce 350 W × 5 hours = 1,750 Wh (1.75 kWh). Thus, with 30 solar panels, the solar power plant would generate 52.5 kWh per day.